Podcasting as an educational building block in academic libraries - Ralph, Jaya; Olsen, Sonja (Australian Library and Information Association, 2007)
Podcasting has taken off in leaps and bounds, having been adopted by many groups for many different purposes from disseminating television programs to making university lectures available. The popularity of podcasting inspired Curtin University Library to develop its own podcast series at the end of 2005. This paper indicates the success of this series to date and demonstrates how podcasts can effectively cater for today's learning styles, how they can benefit distance education and offshore students, and how they have evolved into useful educational tools in the twenty-first century.